ANALISIS MODAL KERJA PADA CV. BAGUS JAYA SANGATTA - Imam Nazarudin Latif2, Iswanto, Elfreda A Lau2, (EKONOMIA, 2015)
This study aims to find out about the use of working capital in the CV. Bagus Jaya particularly in working capital turnover,this study from 2010 to 2012.Resereach activities will be undertaken ,nameely : literature study, field observations, interviews, documentation, data collection, and analysis.theData collected in thus study include : general description cv. Bagus Jaya ,organizational structure,the consolidated balance sheet and income statment.      Formulation of the problem in this study is whether the working capital on the cv.Bagus Jaya in 2011 and 2012 have been efficient ?The hypothesis study is the use of working capital in the CV.Bagus Jaya have efficient. Basic theory used is finansial management,outlines some of the basic theories, hypotheses and conceptual definition.Analyisis tools and research hypotheses used the working capital turn over includes sales and use of working capital.      Results of the analysis showed that the working capital turn over in 2010 amounted to 11,62 times and in 2011 amounted to 12,65 times ,this is caused due to sales in 2011 decreased by 7% while a much larger working  capital decreased by 14% which resulted in an increase working capital turn over.       For working capital turn over in 2012 decreased by 2,46% times to 10,19% this is caused due to in creased working capital by 47% and sales rose only 19% this result working capital turn over in a fall.    Thus,the hypothesis of this study based on the analysis and discussion of the obtained conclusion that working capital 2010 until the  2012 fluctuated so that this hypothesis is rejected.